ANTENATAL INTEREST OF PREGNANT WOMEN IN AWKA DISTRICT, NIGERIA: IMPLICATION FOR CONSELLING - Ada Anyamene; Chinyelu Nnokolo; Nnenna Anyamene (European Scientific Journal, ESJ, 2014)
The major purpose of this research was to study the level of antenatal interest of pregnant women in Awka District of Nigeria. The population for the study was 380 mothers who attended antenatal clinic from April 2012 to September 2013. No sampling was done. All the women who attended antenatal clinic from April 2013 – September 2013 were used for the study. Three research questions and three hypotheses guided the study. The instrument for data collection was researchers made questionnaire which was duly validated by experts. Reliability co-efficient of 0.92 was calculated using test re-test. The collected data were subjected to mean and t-test. The findings indicate there is a significance difference in the level of antenatal interest between urban and rural women. There were also no significant different between the age of the women. Based on the findings the researchers recommended that more counselling should be given to women from rural area on the importance of attending antenatal regularly and show interest.